Crystal structure of [(2R,3R,4S)-3,4-bis(acetyloxy)-5-iodo-3,4-dihydro-2H-pyran-2-yl]methyl acetate - Zukerman-Schpector, J. (International Union of Crystallography, 2015)
In the title compound, C12H15IO7, the 3, 4-dihydro-2H-pyran ring is in a distorted half-boat conformation with the atom bearing the acetyloxy group adjacent to the C atom bearing the methylacetate group lying 0.633 (6) Å above the plane of the remaining ring atoms (r.m.s. deviation = 0.0907 Å). In the crystal, molecules are linked into a supramolecular chain along the a axis through two C - H⋯O interactions to the same acceptor carbonyl O atom; these chains pack with no specific intermolecular interactions between them.